Muscular dystrophies and Ayurveda (AYUSHDHARA, 2025)
Muscular dystrophies (MD) are a group of genetic disorders characterized by progressive muscle weakness and degeneration. Becker Muscular Dystrophy (BMD) being a milder form of X-linked recessive dystrophy caused by a defect in the dystrophin gene. BMD predominantly affects proximal muscles, and its symptoms include muscle weakness, contractures, cardiac involvement, and skeletal deformities. Contemporary medical treatments for muscular dystrophies focus on managing symptoms, using drug therapy, physical therapy, and surgery, although there is no complete relief. Ayurveda offers an alternative perspective, viewing Muscular dystrophies through the lens of Vata Dosha imbalance and genetic defects known as "Beeja Dushti." The disorder is linked to impaired muscle metabolism (Mamsadhatuagni) and blockage in bodily channels (Srotorodha), leading to muscle degeneration. Ayurvedic management aims to restore balance through purification (Shodhana), Shamana oushdhi which is having Brumhana and Balya effect, rejuvenation (Rasayana) therapies, Ekamulika prayoga like Ashwagandha, Kapikacchu, and Bala and Yoga practices further support muscle function and overall vitality. While Ayurveda may not cure the underlying genetic causes, it can help to slow disease progression, improve mobility, and enhance quality of life by addressing metabolic imbalances, eliminating toxins, and promoting tissue regeneration. This holistic approach integrates ancient wisdom with modern scientific insights to offer a comprehensive strategy for managing muscular dystrophy.